Intraspecific kleptoparasitism improves chick growth and reproductive output in Common Terns Sterna hirundo. (13th March 2013) - García, Germán O.; Becker, Peter H.; Favero, Marco; Reynolds, Jim
<x xml:space="preserve">Abstract</x> Kleptoparasitism is a well‐known foraging strategy used opportunistically by many seabirds. Here, we investigated the effect of intraspecific kleptoparasitism on chick growth and reproductive output in Common Terns Sterna hirundo. Effects were compared between two groups comprising (1) individuals using kleptoparasitism during the chick‐rearing period (kleptoparasitic group, n = 18), and (2) individuals in pairs that never performed kleptoparasitism throughout the season ('honest' group, n = 21). The null models best described variation in mass at day 3 and the pre‐fledging mass, indicating no significant effect of the explanatory variables. However, the best models describing the linear growth rate (days 3–13) and peak mass included the parents' foraging strategy (kleptoparasitic vs. honest parents) as an explanatory variable. These two growth parameters were higher in chicks of kleptoparasitic parents. Kleptoparasitic foraging strategy was also associated with higher pre‐fledging survival, as the reproductive performance (i.e. number of fledglings) was significantly higher in the kleptoparasitic than in the honest group. We suggest that by stealing food (and consequently feeding offspring more frequently with high‐quality prey), kleptoparasitic parents are able to produce higher quality chicks with enhanced survival.